(untitled) (European Bison Conservation Newsletter, 2013)
Data on specific and quantitative structure of helminthofauna of European bison (Bison bonasus bonasus) from Borisov-Berezinsky free-living population are presented. Degree of seasonal infection of E. bison by different helminth species is estimated. Ways of infecting an organism by most frequent parasites – Fasciola hepatica and Dictyocaulus filaria are described.